Urothelial carcinoma following kidney transplantation: a narrative review of Chinese insights and challenges from pathogenesis to precision diagnosis and treatment - Li, Lei; Ren, Fei; Liu, Zhuo; Tian, Xiaojun; Zhang, Hongxian; Wang, Guoliang; Zhang, Shudong; Ma, Lulin (Frontiers in Immunology, 2025)
Kidney transplant recipients (KTRs) exhibit a higher incidence of neoplasms compared to the general population, primarily due to the prolonged administration of immunosuppressive agents and viral infections. In China, the primary type of tumor among KTRs is urothelial carcinoma (UC), which lacks specific clinical manifestations. Accurate diagnosis necessitates the integration of multiple diagnostic modalities, while therapeutic approaches must judiciously balance oncological control with the preservation of renal function, thereby presenting a considerable challenge to the health of KTRs. This article provides a comprehensive review of the epidemiological characteristics, risk factors, diagnostic methodologies, and therapeutic strategies associated with urothelial carcinoma post kidney transplantation (KT), aiming to enhance healthcare professionals’ understanding of this condition and improve patient management.